Pengembangan Layanan Perbankan Digital dalam Perbankan Syariah - Riska Selvia; Femei Purnama Sari; Anggun Okta Fitri (Jurnal Bersama Ilmu Ekonomi (EKONOM), 2025)
The development of digital technology has brought major changes in the world of Islamic banking, especially in the way people access financial services. Now, with the advancement of information technology, Islamic banks are able to provide various services that make it easier for people without having to come directly to the bank office. This study aims to determine the extent to which Islamic banking has developed in the digital era, with an emphasis on the role of information technology in improving efficiency and ease of access to financial services. This research uses the library study method, by reviewing various literature and documents related to the topic of Islamic banking and digitalization. Data sources come from books, scientific journals, and other relevant references. In the analysis process, the author uses a descriptive approach to explain the progress achieved by Islamic banking in utilizing digital technology. The findings in this study reveal that digital-based financial services, such as mobile banking and internet banking, play an important role in deepening Islamic banking and internet banking in entering the digital era, which continues to play an important role in expanding public access to Islamic banking products. In addition, Islamic banks have also come up with various innovative features that suit the needs of customers, such as bold account opening, transactions without physical cards, and financial services that are easy to use.